Skin microbiome dysbiosis in leprosy cases - Teng, Vannia C.; Esti, Prima K. (International Journal of Research in Dermatology, 2021)
The human skin possesses a microenvironment conducive to the growth of the skin microbiome, which plays in many physiological functions in cutaneous immunity homeostasis and maturation. The microbiome composition depends on many variables, such as endogenous (host condition) or exogenous (environmental) factors and topographic location. Host-skin microbes’ interaction can be mutualism or pathogenicity. Dysbiosis or alteration in skin microbiota is associated with various dermatological diseases, including leprosy. Dysbiosis is driven by the alteration of the microbial communities themselves or due to the intrinsic features of the host. Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae targeting the nerves and skin, leading to loss of sensation on the skin, with or without dermatologic lesions, and correlated with long term consequences, such as deformities or disability. Microvascular dysfunction and significant alterations in capillary structure due to invasion of M. leprae lead to altered hydration levels of the skin caused by disruption of blood flow; which changes the resident microbial community structure. The skin microbiome composition differences in leprosy patient’s skin lesions were observed; skin microbial diversity in the leprosy patients was lower than in healthy individuals. The diversity reduction was observed in freshly diagnosis leprosy patients, those at various stages of MDT, and post-MDT; indicated that both the interaction between skin microbial community and M. leprae or the ongoing therapeutic regimen impacted the skin microbiome variation.